1984
DOI: 10.1002/jcu.1870120602
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal studies of fetal growth using volume parameters determined with ultrasound

Abstract: To explore the use of three-dimensional parameters in characterizing fetal growth with ultrasound, the accuracy of volume measurements and the ability to make such measurements during pregnancy have been investigated. Total fetal volumes (TOTV) determined with ultrasound in utero were compared to volume measurements obtained by hydrostatic weighing following induced abortion at 19.4 (+/- 1.8 SD) weeks, menstrual age (MA), and to those calculated from birth weights and density values for term fetuses [39.3 (+/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…In our study, we found that males have 1-dimensional traits slightly larger than females, mainly in the 3rd trimester. Similar results are reported in the literature (57,(60)(61)(62). These differences are consistent with the higher birthweight of males, weight being proportional to body volume (i.e.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we found that males have 1-dimensional traits slightly larger than females, mainly in the 3rd trimester. Similar results are reported in the literature (57,(60)(61)(62). These differences are consistent with the higher birthweight of males, weight being proportional to body volume (i.e.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, many investigators have used longitudinal studies to generate standards or reference ranges to monitor fetal growth. These studies have included individual biometric parameters such as fetal head circumference [50-60] and abdominal circumference [50-54,56,58,60-63] as well as computed-estimated fetal weight [50,51] or volumetric parameters such as limb volume [64,65] or fractional limb volume [66-68]. The conceptual basis consists of comparing the trajectory of growth of a particular fetus with that of a standard.…”
Section: Introductionmentioning
confidence: 99%
“…Serial BPD measurements in primates (137) and man (120,138) as well as biochemical data in pregnancy (3) have similarly pointed to ranking or early dictation of a level of growth which subsequently was confined to a narrow centile range. Visual inspection of fetal volume curves obtained by Deter et al (48) suggests the same.…”
Section: Intrauterine Volume Changes In Normal Pregnancymentioning
confidence: 78%